Metodologia para determinação da integridade da Madeira de Edificações Históricas por Meio de Pulsos Ultra-Sônicos - Amanda Rocha Teixeira (2009)
Nowadays the society is more aware of the importance of historical buildings, as the architectural heritage is a significant symbol in the national identity. This concern reflects the maintenance of this heritage and, consequently, brings a greater number of professionals that search for better inspection techniques in the buildings. Thus, the constant inspection becomes important for the maintenance of the historical buildings.Nondestructive testings (NDTs) are the most suitable methods for this inspection, because they do not provide any interference in the architecture of the structural element, keeping the integrity and originality of the work. Among the various existing NDTs, one of the most widespread and promising is the technique of ultrasound. Theobjective of this work was to develop a methodology for inspection of structural elements of wood attacked by xylophagous insects, using ultrasonic pulses. This methodology was applied in three structural elements (three tests) with the objective of finding possible deterioration. Testings 1 and 2 were performed by means of direct transmission of pulses, while the analysis of the parts in Testing 3 were made in anindirect way. By the results obtained in Testing 1 it was possible, by usingisochromatics, to track in the plan the degraded areas of a glued laminated wood beam.The results of Testing 2, developed in locu on a historic wooden structure, helped to improve the methodology that proved to be unsatisfactory for this structure extremely deteriorated because of the retractions that occurred over time. Testing 3, also conducted in an old structural element, was divided in two parts: one test usingtransducers with frequency of 500 kHz and one test using transducers with frequency of 150 kHz. The proposed methodology allows us to find internal deteriorations to historic wooden structures with a high degree of reliability. This study will enable a more accurate and reliable evaluation of wood elements in historic structures, avoiding the unnecessary exchange of healthy structural elements, supposedly damaged, or even the maintenance of extremely deteriorated elements of the structure, that could impair significantly the global stability of the building .